2003
DOI: 10.1002/pon.772
|View full text |Cite
|
Sign up to set email alerts
|

Repressive coping before and after diagnosis of breast cancer

Abstract: Previously found higher repression in cancer patients vs. controls could be a response to the threat associated with cancer diagnosis and may not necessarily reflect premorbid differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
2
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 52 publications
4
35
2
2
Order By: Relevance
“…Our results differ from the findings of a previous study, which did not find a significant difference in perceived risk between women with and without breast cancer [10]. While the two studies were comparable with respect to setting, number of participants, prevalence of cancer, and age, the method used to measure perceived risk was different.…”
Section: Discussioncontrasting
confidence: 85%
“…Our results differ from the findings of a previous study, which did not find a significant difference in perceived risk between women with and without breast cancer [10]. While the two studies were comparable with respect to setting, number of participants, prevalence of cancer, and age, the method used to measure perceived risk was different.…”
Section: Discussioncontrasting
confidence: 85%
“…In one study, lower level of worry during cancer treatment was related to ultimate life satisfaction (37). On the other hand, there are some data indicating that most people show life satisfaction even with very poor health states, such as amputation (38,39), and several studies indicating that survivors of cancers in general and childhood cancers in particular may be biased reporters and tend to deny difficulties and overestimate their positive health and satisfaction (40)(41)(42)(43)(44). O'Leary et al (45) reported from a sample of Dana-Farber patients participating in CCSS that survivors had a strong tendency toward an enhanced self-appraisal and such bias had a differential effect on self-reported physical and emotional quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The innovative aspect of this study is the fact that the evaluation of a psycho-oncologist takes place during the diagnosis and treatment of cancer, and it can uncover hidden psychopathological pathologies that may go unnoticed during the first visit with the oncologist. If these disturbances are not evaluated in time, they could evolve into more severe forms, bringing the patient to emotional disturbances linked to cancer and its therapies, which can become difficult to treat [39][40][41][42].…”
Section: Discussionmentioning
confidence: 98%